2023
DOI: 10.1038/s41598-023-33020-6
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash boosted electrocatalytic properties of PEDOT:PSS counter electrodes for the triiodide reduction in dye-sensitized solar cells

Abstract: Fly ash solid waste from a power plant was applied in a solar cell application for the first time. A doctor blade was used to coat FTO-glass with a composite film of mixed fly ash and PEDOT:PSS (FP). XRD, FTIR, SEM, EDX, and BET analyses were used to elucidate the crystal structure, morphology, and functional groups of fly ash in the current research. A significantly high efficiency solar cell was fabricated utilizing fly ash. CV, Tafel, and EIS analyses indicated a decrease in charge transfer resistance and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The spectrum of pure PEDOT: PSS exhibits a large band at 2900–3500 cm −1 associated with –OH stretching from PSS moieties and –CH 2 asymmetric stretching. 52,53 The peak around ∼1640 cm −1 and ∼1025 cm −1 are assigned to CC and C–C stretching of the phenyl side group and quinoid ring in EDOT. 54,55 C–O–C bond stretching of ethylenedioxy group are observed at ∼1370 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of pure PEDOT: PSS exhibits a large band at 2900–3500 cm −1 associated with –OH stretching from PSS moieties and –CH 2 asymmetric stretching. 52,53 The peak around ∼1640 cm −1 and ∼1025 cm −1 are assigned to CC and C–C stretching of the phenyl side group and quinoid ring in EDOT. 54,55 C–O–C bond stretching of ethylenedioxy group are observed at ∼1370 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the addition of HCl to activated fly ash caused a decrease in the transmittance intensity in the FTIR spectra because the acid could damage the structure of the -OH group so that the bound water molecules were released. 23 Then, the fly ash preparation showed an absorption band at wave number 2923.25 cm -1 which was the C-H stretching vibration 24 . This showed that fly ash still contained impurities, namely carbon bonds.…”
Section: Ftirmentioning
confidence: 99%
“…[32][33][34] Additionally, the presence of the peaks originating from the Si-O bond at 1072 cm À1 , 773 cm À1 and 437 cm À1 indicate the presence of the cross-linker GOPS in the aerogel. 35,36 The distinctly attenuated peak of SDBS at 590 cm À1 indicates the removal of SDBS by solvent treatment. The resulting PSG aerogel showed notable features of ultra-softness and ultra-lightweight (Fig.…”
Section: Design and Fabricationmentioning
confidence: 99%